Cover Jurnal Fitopatologi Vol. 18 No. 2, Maret 2022 - Editors (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2022)
This editorial contains the front cover, editorial page, and back cover of the Indonesian Journal of Phytopathology Vol. 18 No. 2, Maret 2022